The Buck Stops Here Critical Incidents in School Governance as Interpreted by Superintendents - Bryant, Miles T.; Grady, Marilyn L. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
This study explores conflict between school superintendents and board members as perceived by superintendents. A critical incident methodology as elaborated by Flanagan was used to isolate and examine conflict. Common types of conflict include problems with family and friends, personal agendas, hiring and firing problems, and role uncertainty. Findings suggest that board members' private interests (as defined by superintendents), combined with superintendents' ingrained expectations regarding a proper corporate model of school governance, contribute to a dysfunctional conflict in the school policy domain. Both the expression of private interests and the superintendents' expectations impede role negotiation, a natural part of the superintendent/board member relationship. Helping school district officials and administrators make conflict more constructive requires changes in assistance to boards and in the preparation and socialization of school administrators. (30 references) (MLH)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Education; Board Administrator Relationship; Conflict; Elementary Secondary Education; Expectation; Role Conflict; School Administration; Superintendents; Role Ambiguity; Reports, Evaluative